2018
DOI: 10.1007/s00787-018-1161-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term social skills group training for children and adolescents with autism spectrum disorder: a randomized controlled trial

Abstract: Social skills group training (SSGT) is widely used for intellectually able children and adolescents with autism spectrum disorder (ASD). Previous studies indicate small to moderate effects on social communication capacities. The duration of most available programs is relatively short, and extended training might lead to further improvement. This randomized controlled trial compared an extended 24-week version of the SSGT program KONTAKT with standard care. The weekly sessions gradually shifted in content from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 33 publications
1
92
1
Order By: Relevance
“…Thirty-two studies used integrative programs [18,20,24,25,28,30,33,[35][36][37]40,52,58,60,62,63,71,74,[77][78][79]81,86,89,92,96,98,[100][101][102][103]107]. Also, thirty studies used social skills development interventions [16,17,19,22,23,29,32,34,38,39,45,47,48,56,57,59,61,64,65,69,72,73,80,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two studies used integrative programs [18,20,24,25,28,30,33,[35][36][37]40,52,58,60,62,63,71,74,[77][78][79]81,86,89,92,96,98,[100][101][102][103]107]. Also, thirty studies used social skills development interventions [16,17,19,22,23,29,32,34,38,39,45,47,48,56,57,59,61,64,65,69,72,73,80,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 studies on the social skills development intervention approach, 28 studies were signi cantly reached in all outcomes. 32 studies only examined the impact of the intervention on the social skills of the participants [16,17,22,23,29,32,34,39,47,48,59,64,65,69,72,73,80,[83][84][85]90,99,105], three studies on behavior and social skills [45,57,97], one study on social motivation [38], and one study on social engagement [61]. But, only two studies reported that some of the expected outcomes created signi cant change [19,56].…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that a long version of KONTAKT (24-weeks) resulted in larger effects in general than we have found for the 12weeks version used here. 45 Unfortunately, that trial was not sufficiently powered for subgroup analyzes.…”
Section: Discussionmentioning
confidence: 99%
“…The manual and work material should be user-friendly, accessible, and easy to adapt/revise. We viewed the length of the intervention as a trade-off between the optimal effect, available resources, and demands on the participant's time and effort [62]. To be effective, we reasoned that the duration should enable the participants to pursue and attain meaningful goals in the course of the intervention.…”
Section: Developmentmentioning
confidence: 99%